Common Fixed Points of Generalized Cocyclic Mappings in Complex Valued Metric Spaces - Mujahid Abbas; Manuel De la Sen; Talat Nazir (Discrete Dynamics in Nature and Society)
We present fixed point results of mappings satisfying generalized contractive conditions in complex valued metric spaces. As an application, we obtain a common fixed point of a pair of weakly compatible mappings. Some common fixed point results of generalized contractive-type mappings involved in cocyclic representation of a nonempty subset of a complex valued metric space are also obtained. Some examples are also presented to support the results proved herein. These results extend and generalize many results in the existing literature.